2006
DOI: 10.1196/annals.1371.067
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality in an Area of Campania (Italy) Characterized by Multiple Toxic Dumping Sites

Abstract: Several recent studies have documented that a widespread practice of dumping toxic wastes has taken place for many years in the Provinces of Naples and Caserta. Extensive programs of environmental monitoring are currently ongoing in the area. In this frame, the Department of Civil Defence of the Italian Government has appointed an ad hoc study group in order to assess the health status of the population resident in the area of interest. The first investigation performed by the study group has been a geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 43 publications
5
48
1
Order By: Relevance
“…Such an index was built on figures from the 1991 Population Census and estimated at a municipal level. 20 Significant clustering of mortality by specific cancers (lung, liver, gastric, kidney and bladder) and prevalence of total and specific malformations (limb, cardiovascular, urogenital systems) were described in the northern part of Naples and southern part of Caserta Provinces, thus confirming the results by Comba et al [8][9] In the study by Martuzzi and co-authors, the intensity of waste-related exposure, as assessed throughout a composite index used at a municipality level, appeared to be correlated with several health outcomes. The waste index (WI) was built on data from the regional Environmental Protection Agency (including both authorized landfills and illegal waste dumping sites) and from the Italian National Institute of Statistics (ISTAT) 1991 Population Census.…”
Section: Evidence Linking Cancer Mortality and Congenital Anomalies Tsupporting
confidence: 80%
See 2 more Smart Citations
“…Such an index was built on figures from the 1991 Population Census and estimated at a municipal level. 20 Significant clustering of mortality by specific cancers (lung, liver, gastric, kidney and bladder) and prevalence of total and specific malformations (limb, cardiovascular, urogenital systems) were described in the northern part of Naples and southern part of Caserta Provinces, thus confirming the results by Comba et al [8][9] In the study by Martuzzi and co-authors, the intensity of waste-related exposure, as assessed throughout a composite index used at a municipality level, appeared to be correlated with several health outcomes. The waste index (WI) was built on data from the regional Environmental Protection Agency (including both authorized landfills and illegal waste dumping sites) and from the Italian National Institute of Statistics (ISTAT) 1991 Population Census.…”
Section: Evidence Linking Cancer Mortality and Congenital Anomalies Tsupporting
confidence: 80%
“…In these areas, the presence of numerous dumping sites (both legal and illegal) has been repeatedly documented. [8][9][10][11][12]22 Though suggestive of a contributory role of waste exposure in determining health outcomes in the identified areas, these findings are far from being conclusive relatively to the causative nature of the association observed. In the first place, the adopted study designs do not allow causal inference.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cardile et al 2004;Comba et al 2006;Carbone et al 2011;Andreozzi et al 2009;Hendrickx 2009). Case et al (2011) showed that for more than three decades, it has been considered by scientific panels for government agencies (Agency for Toxic Substances and Disease Registry [ATSDR] 2003) that fibers shorter than 5 μm in length have insignificant carcinogenic potential, and that the risk for the health increases with exposure to longer fibers (for lung cancer, fibers longer than 20 μm and thinner than 0.3 μm are of particular concern as demonstrated by e.g.…”
Section: Introductionmentioning
confidence: 91%
“…However, the association between hazardous wastes exposure and health effects has been discussed in several studies [8]. Obviously, a separate discussion should be held concerning the health and environmental impacts of illegal waste management practices (e.g., illegal waste burying in areas not designated as waste dump sites and illegal waste burning and the fires), which can also have an impact on the environment and health, with a number of documented cases [9,10]. In any case, the abovementioned associations can be considered as relevant only when defined in rigorously conducted epidemiology studies [8].…”
Section: Introductionmentioning
confidence: 99%